Climate-smart tools for Latin America - International Center for Tropical Agriculture (2015)
The combined effects of climate change, inequity, and population pressures are escalating the challenges faced by Latin America’s smallholder farmers. CIAT and CCAFS, in collaboration with many other partners, have developed a comprehensive set of tools, tailored to the region, to rapidly scale-up the adoption of CSA practices by smallholders for improved food and livelihood security and resilience to climate change. These factsheets describe CSA tools including: CSA Prioritization Framework; Targeting CSA portfolios: Ex-ante impact assessment and tradeoffs; CSA-Plan; CSA Wizard; CSA Rapid Assessment; Agroclimate services; Climate Analogues; Terra-I; 5Q Approach; CCAFS Climate Portal; CSA Implementer, and scaling CSA in value chains.